Primary School Students’ Online Learning During Coronavirus Disease 2019: Factors Associated With Satisfaction, Perceived Effectiveness, and Preference - Zheng, Xiaoxiang; Zhang, Dexing; Lau, Elsa Ngar Sze; Xu, Zijun; Zhang, Zihuang; Mo, Phoenix Kit Han; Yang, Xue; Mak, Eva Chui Wa; Wong, Samuel Y. S. (Frontiers in Psychology, 2022)
Emergency online education has been adopted worldwide due to the COVID-19 pandemic. Prior research regarding online learning predominantly focused on the perception of parents, teachers, and students in tertiary education, while younger children’s perspectives have rarely been examined. This study investigated how family, school, and individual factors would be associated with primary school students’ satisfaction, perceived effectiveness, and preference in online learning during COVID-19. A convenient sample of 781 Hong Kong pupils completed an anonymous online survey from June to October 2020. Logistics regression was conducted for 13 potential factors. Results indicated that only 57% of students were satisfied with their schools’ online learning arrangement, and 49.6% regarded online learning as an effective learning mode. Only 12.8% of students preferred online learning, while 67.2% preferred in-person schooling. Multiple analysis suggested that teacher-student interaction during online classes were positively associated with students’ satisfaction, perceived effectiveness, and preferences in online learning. Compared to grade 1-2 students, grade 3-6 students perceived more effectiveness and would prefer online learning. Happier schools were more likely to deliver satisfying and effective online education. Students who reported less happiness at school would prefer online learning, and students who reported less happiness at home would be less satisfied with online learning and reflected lower effectiveness. Teachers are encouraged to deliver more meaningful interactions to students and offer extra support to younger children during online classes. Primary schools and parents are encouraged to create a healthy and pleasant learning environment for children. The government may consider building up happy schools in the long run. The study findings are instrumental for policymakers, institutions, educators, and researchers in designing online education mechanisms.